New Energy Sources for Jordan : Macroeconomic Impact and Policy Considerations - Gamba, Andrea (IMF Working Papers; Working Paper ;, 2015)
Jordan's initiatives to reduce its energy dependency could have substantial macroeconomic implications, but will crucially depend on the level of international oil prices in the next decade. Significant uncertainties remain regarding the feasibility of the initiatives and their potential fiscal costs, including from contingent liabilities, could be very large. Given the lead time required for such major investments, work should start now on: (i) conducting comprehensive cost-benefits analysis of these projects; (ii) addressing the challenges arising from the taxation of natural resources; and (iii) designing a fiscal framework to anchor fiscal policies if revenue from these energy projects materializes.